Is neoadjuvant chemotherapy followed by surgery the appropriate treatment for esophagogastric signet ring cell carcinomas? A systematic review and meta-analysis - Schiefer, Sabine; Crnovrsanin, Nerma; Kalkum, Eva; Vey, Johannes A.; Nienhüser, Henrik; Rompen, Ingmar F.; Haag, Georg M.; Müller-Stich, Beat; Billmann, Franck; Schmidt, Thomas; Probst, Pascal; Klotz, Rosa; et al. (Frontiers in Surgery, 2024)
The impact of neoadjuvant chemotherapy (nCTX) on survival and tumor response in patients with esophagogastric signet ring cell carcinoma (SRCC) is still controversial.Two independent reviewers performed a systematic literature search in Medline, CENTRAL, and Web of Science including prospective and retrospective two-arm non-randomized and randomized controlled studies (RCTs). Data was extracted on overall survival (OS) and tumor regression in resected esophagogastric SRCC patients with or without nCTX. Survival data was analyzed using published hazard ratios (HR) if available or determined it from other survival data or survival curves. OS and histopathological response rates by type of tumor (SRCC vs. non-SRCC) were also investigated.Out of 559 studies, ten (1 RCT, 9 non-RCTs) were included in this meta-analysis (PROSPERO CRD42022298743) investigating 3653 patients in total. The four studies investigating survival in SRCC patients treated with nCTX+surgery vs. surgery alone showed no survival benefit for neither intervention, but heterogeneity was considerable (HR 1.01; CI 0.61-1.67; p=0.98; I 2 =89%). In patients treated by nCTX+surgery SRCC patients showed worse survival (HR 1.45; CI 1.21-1.74; p<0.01) and lower rate of major histopathological response than non-SRCC patients (OR 2.47; CI 1, p<0.01).The current meta-analysis could not demonstrate beneficial effects of nCTX for SRCC patients. Histopathological response to and survival benefits of non-taxane-based nCTX seem to be lower in comparison to non-SRC esophagogastric cancer. However, certainty of evidence is low due to the scarcity of high-quality trials. Further research is necessary to determine optimal treatment for SRCC patients.